Influence of Digital Marketing on Hospital and Patient Loyalty in Makassar Hospital - Nurfardiansyah Burhanuddin; Darmawansyah; Syahrir A Pasinringi; Ridwan Amiruddin; Dewi Rizki Nurmala (International Journal of Medical Toxicology and Legal Medicine, 2024)
Background: Competition in the industry is becoming more strict, demanding, and sick. In order to adopt effective marketing strategies, patients’ loyalty needs to be maintained. Digital marketing is becoming one of the main solutions in improving the patients’ experience as the direct contributors to patient loyalty. Objective: This research aims to analyze the influence of digital marketing on hospital patients’ loyalty in Makassar. Method: The method applied in this study is analytical correlation with cross-sectional design. In this case, current research was done in three hospitals in Makassar, including Wahidin Sudirohusodo General Hospital, Stella Maris Hospital, and Hasanuddin University Hospital, from March to June 2024. Furthermore, the population involved is all patients who used general payment method. In this case, the sampling was done using proportionate stratified random sampling, with total samples selected is 393 patients. Primary data were collected through questionnaires and interviews, while secondary data were obtained from literature and agencies related. Data analysis was further carried out using the SPSS program, through univariate and bivariate analysis techniques. Results: Research results reveals that there is a connection between digital marketing and patient loyalty with a significant value (0.000). Overall, this study confirms the importance of implementing effective digital marketing to increase the patients’ loyalty at hospital. Conclusion: This study concludes that digital marketing at home has a significant influence on patient loyalty through patient experience. Effective digital marketing, which includes the use of social media, websites, and mobile applications, is capable of increasing patient experience, which in turn strengthens patient loyalty. Although patients’ experience affects loyalty indirectly, results show that digital marketing provides a big contribution to creating a positive experience that influences satisfaction and commitment of the patients.